2012
DOI: 10.5505/tjtes.2012.76402
|View full text |Cite
|
Sign up to set email alerts
|

Late-diagnosed bilateral intertrochanteric femur fracture during an epileptic seizure

Abstract: Although spontaneous and simultaneous bilateral hip fractures without trauma are seen rarely, epileptic seizures may lead to these fractures. We present an 82-year-old female patient with poor bone quality and a 20-year history of epilepsy. She had been using anticonvulsant drugs for almost 20 years. Following a convulsive epileptic attack, bilateral intertrochanteric femur fractures occurred (causing bilateral hip pain), which was diagnosed on the 12th day. An earlier pelvic anteroposterior roentgenogram woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In addition to trauma, bilateral fractures due to epilepsy and electrocution have been described [8]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to trauma, bilateral fractures due to epilepsy and electrocution have been described [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Types of fractures reported during seizures most commonly include fractures of thoracic and lumbar vertebrae [46], therefore fractures should be examined for in the acute setting [47], particularly to avoid late detection and management [48]. Potentially serious complications have been published including case reports of a patient with a burst lumbar vertebral fracture during seizure which resulted in acute cauda equina / conus medullaris syndrome [46], and bilateral acetabular fractures and left proximal humerus fracture [49].…”
Section: Fracturesmentioning
confidence: 99%
“…However, results of studies have suggested variation in the mechanisms of fracture, including that there is also higher risk of fracture through mechanisms other than seizures, and that monitoring for neurotoxicity is also important [116]. In the acute setting in post-ictal patients, the possibility of fracture should be considered on history and examination [47], and if there is clinical suspicion of fracture, relevant investigation, management and referrals should be requested, to avoid late detection [48]. Physician and patient education regarding bone disease and fracture risk in association with epilepsy will be important [33,32], as well as education regarding bone protective strategies [117,118], and being aware of (and successfully navigating) barriers to receiving appropriate screening and management of bone health in epilepsy care [119].…”
Section: Managementmentioning
confidence: 99%
“…The muscular forces involved in the tonic-clonic phase of convulsive seizures are demonstrated by the occurrence of bone fractures in the spinal column and proximal skeleton [9]. Various fractures have been noted as resulting from convulsive seizures, including fractures of the vertebrae, pelvis, femoral neck and shoulder [9, 10, 11, 12, 13, 14]. Most vertebral fractures are compression fractures, but burst fractures with neurological complications can occur [15].…”
Section: Introductionmentioning
confidence: 99%